“Knaller-Sex für alle”: Popfeminist Body Politics in Lady Bitch Ray, Charlotte Roche, and Sarah Kuttner - Carrie Smith-Prei (Studies in 20th & 21st Century Literature, 2011)
Germany has seen a recent upsurge in publications proclaiming that feminism is again an urgent matter for a new generation of women. Faced with the reactionary demography debate and the hegemony of second-wave feminism, young writers, musicians, journalists, and critics call for new models of feminism relevant to women today. As one of these viable models, popfeminism draws on dominant trends in mass culture, on pop’s forty-year history as a cultural prefix in Germany, and on traditional feminism in order to create a new, ostensibly apolitical, feminist subculture based in self-stylization and individual autonomy. Shared by many popfeminist sources is the depiction of negatively coded female corporeality. This article begins with a theoretical analysis of writings on sexuality and the body in recent (pop)feminist nonfiction. It then examines the negative corporeal self-stylizations in Turkish-German rapper Lady Bitch Ray’s performances since 2006, in former music video host Charlotte Roche’s novel Feuchtgebiete (2008), and in media personality Sarah Kuttner’s novel Mängelexemplar (2009). Ultimately, these negatively coded bodies are shown to uncover popfeminism’s political intent.
Keywords: feminism; German feminism; German-speaking world; relevancy; popfeminist; popfeminism; sexuality and the body; rapper; Turkish-German rapper; Lady Bitch Ray; Charlotte Roche; Feuchtgebiete; Sarah Kuttner; Mängelexemplar; negatively coded bodies